Description of Eupoa liaoi sp. nov. from China (Araneae: Salticidae) - Peng, Xian-Jin; Li, Shu-Qiang (Zootaxa, 2006)
A new species of jumping spider, Eupoa liaoi sp. nov., is described from Hainan, South-China. Detailed morphological characteristics and illustrations of body and copulatory organs are presented.